The Education of Gifted in Special Education Domain and the Role of ICTs - Drigas, Athanasios; Kontopoulou, Maria-Theofania; Gougoudi, Athanasia; Kantzavelou, Krystallenia; Mertzioti, Louiza (Technium Education and Humanities, 2022)
Gifted and talented students do not constitute one homogenious group. This fact evokes the need for the definition of their characteristics and identification of this population. Undoubtedly metacognitive skills can lead one to recognize his/her strengths and weaknesses and lead him/herself to the upper levels of the pyramid of knowledge. Moreover, identification of giftedness at school requires more than IQ tests, as it is multidimensional. Research argues that early identification and intervention are crucial due to fulfilling their needs for education. Furthermore, early detection of giftedness for students with special needs provides equal opportunities to dual strength students.